2017
DOI: 10.1152/ajprenal.00557.2016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of angiotensin-(1–7) on the exchanger NHE3 and on [Ca2+]iin the proximal tubules of spontaneously hypertensive rats

Abstract: The acute effects of angiotensin-1-7 [ANG-(1-7)] on the reabsorptive bicarbonate flow (J[Formula: see text]) were evaluated using stationary microperfusion in vivo in the proximal tubules of spontaneously hypertensive rats (SHR) and their normotensive controls, Wistar-Kyoto (WKY) rats, using a microelectrode sensitive to H In WKY rats, the control J[Formula: see text] was 2.40 ± 0.10 nmol·cm·s ( = 120); losartan (10 M) or A779 (10 M, a specific Mas antagonist), alone or in combination with losartan, decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 78 publications
(106 reference statements)
0
11
1
Order By: Relevance
“…High-dose Ang (1-7) (10 −6 mmol L −1 ) inhibited NHE 3 activity also in SHR. 30 However, the initial dose-response experiments performed in this study did not detect any biphasic effects of Ang (1-7) on RBF and Na + excretion in neither controls nor diabetics.…”
Section: Discussioncontrasting
confidence: 60%
“…High-dose Ang (1-7) (10 −6 mmol L −1 ) inhibited NHE 3 activity also in SHR. 30 However, the initial dose-response experiments performed in this study did not detect any biphasic effects of Ang (1-7) on RBF and Na + excretion in neither controls nor diabetics.…”
Section: Discussioncontrasting
confidence: 60%
“…Mas is G-protein coupled receptor, which acts through cAMP/PKA pathways to regulate and phosphorylate its substrates on specific serine and threonine residues, e.g., phosphorylation of calcium channel. Recent studies demonstrated that Ang (1–7) increased intracellular calcium levels in microperfused proximal tubular cells, which was markedly inhibited by A779 9 , 10 . The stimulated increase of [Ca 2+ ] i by Ang (1–7) was likely attributed to influx of extracellular calcium, since a membrane impermeable calcium chelator that binds extracellular calcium ions markedly abolished Ang (1–7)-induced increased [Ca 2+ ] i 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Potential downstream signaling pathways of Mas stimulated by Ang (1–7) and related analogs include the phospholipase A2 and the phosphoinositide 3-kinase/AKT pathway, as well as the phospholipase C and Ca 2+ signaling pathway 8 . Recent studies demonstrated that Ang (1–7) increased intracellular calcium levels in microperfused proximal tubular cells, which was markedly inhibited by A779 9 , 10 , an antagonist of Mas. In general, ACE2-Ang (1–7)-Mas receptor axis counteracts the classical RAS (e.g., angiotensin-II), resulting in vasodilation, anti-inflammation, anti-fibrosis, and anti-apoptosis, conferring beneficial effects in the settings of cardiovascular diseases 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well known that Ang (1-7) produces its effects by binding to MasR and MrgD (Santos et al, 2003; Tetzner et al, 2016), early cell culture studies have reported some actions of Ang-(1-7) were mediated via the subtypes of AT1R (Muthalif et al, 1998; Heitsch et al, 2001). Some studies also proposed that MasR may interact with AT1R by receptor hetero-dimerization or alterations in post-receptor signaling (Castro et al, 2005; Kostenis et al, 2005; Tesanovic et al, 2010; Castelo-Branco et al, 2017; O’Neill et al, 2017), which in turn leads to the inhibition of Ang II activity while promoting those of Ang-(1-7). Conversely, many studies have shown that Ang-(1-7) has a low binding affinity to AT1R compared to Ang II (Rowe et al, 1995; Tallant et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Ang-(1-7) has opposing effects to those produced by Ang II, including vasodilatory and anti-fibrotic properties, and has been shown to be protective in cardiovascular and renal tissues (Ferreira and Santos, 2005; Castelo-Branco et al, 2017; O’Neill et al, 2017). Although MasR has been shown to be the putative receptor for Ang-(1-7), it has also been proposed that MasR may interact with other angiotensin receptors such as AT1R and AT2R (Benter et al, 1993; Muthalif et al, 1998; Castro et al, 2005; Kostenis et al, 2005; Tesanovic et al, 2010; Castelo-Branco et al, 2017; O’Neill et al, 2017). However, we and others have recently reported that Ang-(1-7)-MasR axis is upregulated in the splanchnic circulation of cirrhotic animals and cirrhotic patients (Vilas-Boas et al, 2009; Grace et al, 2013).…”
Section: Introductionmentioning
confidence: 99%